Odpowiedzi

2009-11-19T16:23:58+01:00
Oblicz wartość wyrażenia b2( do kwadratu) - 4ac dla :
a)a= 2,b=-3 i c= -2
b)a=1, b=1/4 i c= - 1/2
c)a= -0,2, b= -1 i c= -0,3
d)a= - 3/8, b= o,5 i c 1


a)9+16=24
b) 1/16 +2=2i1/16
c)1-0,24=0,76
d)0,25+1,5=1,75
4 3 4
2009-11-19T16:35:09+01:00
A) (-3x2)do kwadratu - 4x2x(-2) = (-3x2)(-3x2) - 10 = 9 - 6 - 6 + 4 - 10 = -9
b) (0.25x2)(0.25x2) - 4x1x(-0.5) = 0.0625 + 0.5 + 0.5 + 4 - (-2) = 7,0625
c) (-1x2)(-1x2) - 4x(-0.2)x(-0.3) = 1 - 2 - 2 + 4 - 0.24 = 0.76
d) (0.5x2)(0.5x2) - 4x(-0.375)x1 = 0.25 + 1 + 1 + 4 - (-1.5) = 7,75 = 7 i 3/4

Mam nadzieję, że pomogłam ;)) Pozdrawiam
5 3 5